THE APPLICATION OF A REALISTIC MATHEMATICS LEARNING MODEL IN IMPROVING PRIMARY SCHOOL STUDENT LEARNING OUTCOMES IN BANDA ACEH CITY - Teuku Mahmud; Sariakin Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to improve and improve learning outcomes in the learning process which leads to improving mathematics learning outcomes by implementing the Realistic Mathematics Learning Approach implemented by researchers at SD Negeri 15 Banda Aceh City. The subjects in this research were 35 grade IV students and the object of this research was realistic mathematics learning for the 2024/2025 academic year. From the results of data analysis, it shows that during the pre-test before the action was taken, out of 35 students, there were 2 students who completed the study with an average class score of 35.85 and a classical completion level of 5.71%. Furthermore, in cycle I, after implementing realistic mathematics learning, the average class score increased to 68.28 with a classical completion level of 65.71% and the number of students who completed it was 23 students. And after the actions were taken and the second cycle post test was given, learning results were obtained with the class average value increasing to 77.57 and 31 people completed it with a classical completion level of 88.57%. From the results of observations that have been made, it shows that in the first cycle of analysis the achievement obtained by teachers was 2.76 and students obtained 2.44, which means it was still in the poor category. In cycle II, the data from student and teacher observations improved to good. Where the good activity category increased from 2.76 to 3.70 for students and from 2.44 to 3.44 for teachers. Based on the results of this research, it can be concluded that the application of a realistic mathematics learning model can improve student learning outcomes in the operational material for calculating the addition of fractions in class IV of SD Negeri 15 Banda Aceh City.